PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PEMBALUT MEREK KOTEX DI KOTA BATAM - Syarifah Aini Ma'ruf; Tiurniari Purba (LPPM Universitas Putera Batam, 2026)
This study aims to analyze the influence of product quality and brand image on purchasing decisions for Kotex brand sanitary napkins. This study used a quantitative approach with a survey method of 100 respondents who used Kotex sanitary napkins. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis with t-tests and F-tests. The results showed that partially, product quality had no significant effect on purchasing decisions, while brand image had a significant effect on purchasing decisions for Kotex brand sanitary napkins. Simultaneously, product quality and brand image had a significant effect on purchasing decisions. This finding indicates that brand image plays a more dominant role than product quality in driving consumer purchasing decisions.